Immunity-Related Gene Signature Identifies Subtypes Benefitting From Adjuvant Chemotherapy or Potentially Responding to PD1/PD-L1 Blockage in Pancreatic Cancer - Qian, Hao; Li, Hongzhe; Xie, Junjie; Lu, Xiongxiong; Li, Fanlu; Wang, Weishen; Tang, Xiaomei; Shi, Minmin; Jiang, Linxi; Li, Hongwei; Chen, Hao; Peng, Chenghong; et al. (Frontiers in Cell and Developmental Biology, 2021)
Tumor microenvironment comprises of a variety of cell types, which is quite complex and involved in chemotherapy and immune checkpoint blockage resistance. In order to explore the mechanisms involved in tumor immune microenvironment in pancreatic ductal adenocarcinoma (PDAC), we first constructed an immunity-related 18-gene signature using The Cancer Genome Atlas (TCGA) PDAC project data. Then we applied the 18-gene signature to divide PDAC patients into low score and high score groups. Patients in high score group showed inferior prognosis, which was validated in another four independent cohorts, including Ruijin cohort. High score group showed significant enrichment of pathways involved in cell division and cell cycle especially in G1/S phase transition. In high score group, IHC analysis revealed higher levels of the proliferative indexes of Ki67 and PCNA than that in low score group. Prognostic analysis confirmed that patients in high score group could benefit from the gemcitabine-based adjuvant chemotherapy. In low score group, the programmed cell death 1 ligand 1(PD-L1) (+) cases showed worse prognosis but higher T cell infiltration than PD-L1(−) cases. Our immunity-related 18-gene signature could effectively predict PDAC prognosis, and it might be a practical predictive tool to identify PDAC subtype benefitting from gemcitabine-based adjuvant chemotherapy or potentially responding to PD1/PD-L1 blockade therapy.